Work-related behaviour and experience patterns of nurses - Götz, Katja; Beutel, Sabine; Trierweiler-Hauke, Birgit; Mahler, Cornelia; Müller, Gisela (International nursing review, 2012)
Goetz K., Beutel S., Mueller G., Trierweiler-Hauke B. & Mahler C. (2011) Work-related behaviour and experience patterns of nurses. International Nursing Review59, 88-93 Introduction. Nursing working conditions are characterized by heavy workloads and extensive responsibilities. The aim of our study was to report and to compare the actual conditions of work-related behaviour and experience patterns of nurses working on intensive care units (ICUs) and intermediate care in a reference sample of nurses. Methods: The study was designed as a cross-sectional survey with a sample of ICU and intermediate care nurses in one hospital in Germany and a reference sample of nurses (n = 378). Data were analysed regarding 11 health-relevant dimensions and four behaviour patterns examined by the questionnaire ‘Work-Related Behaviour and Experience Patterns’. Group comparison was evaluated with independent t-test. The survey also collected demographic data. Results: In total, 86 of 158 questionnaires (54.4%) were returned. ICU and intermediate care nurses mainly differed in the health dimensions ‘career ambition’ and ‘satisfaction with work’, and had equal mean scores in ‘experiences of social support’. The most common pattern for the majority in our sample was the withdrawal pattern (46.8 %). 17.7% showed the burnout pattern. One third of our sample showed a healthy pattern (25.3%). Conclusions: It was possible to identify clear risk patterns for our sample of ICU and intermediate care nursing staff and to demonstrate that an essential aim should be to minimize the risk of burnout by strengthening nurses' individual, as well as work-related resources by applying a salutogenic approach. Leadership should reinforce motivational aspects to prevent staff withdrawal and to keep nurses in the workforce.